1999
DOI: 10.1016/s0197-4580(99)00022-6
|View full text |Cite
|
Sign up to set email alerts
|

Age-related metabolite changes and volume loss in the hippocampus by magnetic resonance spectroscopy and imaging☆

Abstract: Magnetic resonance imaging (MRI) studies have produced controversial results concerning the correlation of hippocampal volume loss with increasing age. The goals in this study were: 1) to test whether levels of N-acetyl aspartate (NAA, a neuron marker) change in the hippocampus during normal aging and 2) to determine the relationship between hippocampal NAA and volume changes. Proton magnetic resonance spectroscopic imaging (1H MRSI) and MRI were used to measure hippocampal metabolites and volumes in 24 health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
85
1
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(97 citation statements)
references
References 38 publications
9
85
1
2
Order By: Relevance
“…One of the major factors associated with hippocampal changes is age. The age association has been demonstrated in several studies with cross-sectional (Lim et al, 1990, Coffey et al, 1992, Pfefferbaum et al, 1994, Sullivan et al, 1995, De Leon et al, 1997, Schuff et al, 1999, Jernigan et al, 2001, Scahill et al, 2003, Sullivan et al, 2005 and longitudinal (Jack et al, 1998, Scahill et al, 2003, Raz et al, 2004b, Du et al, 2006 designs. Recent research based on magnetic resonance imaging (MRI) has also demonstrated that a spatial mapping method could enhance the detection of the subtle changes in volumetric information and the understanding of age effects on specific regions of hippocampi (Janke et al, 2001, Wang et al, 2003, Thompson et al, 2004, Chetelat et al, 2005.…”
Section: Introductionmentioning
confidence: 85%
“…One of the major factors associated with hippocampal changes is age. The age association has been demonstrated in several studies with cross-sectional (Lim et al, 1990, Coffey et al, 1992, Pfefferbaum et al, 1994, Sullivan et al, 1995, De Leon et al, 1997, Schuff et al, 1999, Jernigan et al, 2001, Scahill et al, 2003, Sullivan et al, 2005 and longitudinal (Jack et al, 1998, Scahill et al, 2003, Raz et al, 2004b, Du et al, 2006 designs. Recent research based on magnetic resonance imaging (MRI) has also demonstrated that a spatial mapping method could enhance the detection of the subtle changes in volumetric information and the understanding of age effects on specific regions of hippocampi (Janke et al, 2001, Wang et al, 2003, Thompson et al, 2004, Chetelat et al, 2005.…”
Section: Introductionmentioning
confidence: 85%
“…In our case we added age to the diagnostic index derived from each metabolite ratio. The reason is that age is a potentially significant factor associated with brain as changes in metabolites reflecting aging are similar to those related to HIV (Chang et al 1996;Schuff et al 1999;Chang et al 2004). Incorporation of aging into the diagnostic procedure, slightly increased the accuracy of the combined index although this increase did not reach statistical significance.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, it has been suggested that decrease in NAA values may also reflect the magnitude of neuronal injury and metabolic dysfunction. Decrease in NAA in the hippocampus has been reported in several conditions, including PTSD (Schuff et al, 1997a), epilepsy (Ende et al, 1997), Alzheimer's disease (Schuff et al, 1997b) and normal aging (Driscoll et al, 2003a(Driscoll et al, , 2005Schuff et al, 1999).…”
Section: Biochemical Changesmentioning
confidence: 99%
“…Many MRS studies in humans report general age-related alterations of the aforementioned metabolites (Chang et al, 1996;Fukuzako et al, 1997), whereas others are more specific to hippocampal metabolite changes associated with volume loss (Schuff et al, 1999). Studies in different patient cohorts (Brooks et al, 1997Jung et al, 1998) and normal populations using quantitative spectroscopy and an extensive neurocognitive battery reveal a significant relationship between neurochemical markers of brain integrity and brain function.…”
Section: Biochemical Changesmentioning
confidence: 99%